Alternative Copolymerization of a Conjugated Segment and a Flexible Segment and Fabrication of a Fluorescent Sensing Film for HCl in the Vapor Phase. Issue 1 (10th October 2012) - Wang, Hongyue; Cui, Hong; Liu, Xinglei; Li, Lanlan; Cao, Yuan; Liu, Taihong; Fang, Yu
Abstract A novel fluorescently active co‐oligomer (P1) was designed and prepared by alternative co‐polymerization of oligo(p‐phenyleneethynylene) (OPE), possessing two cholesterol‐containing side chains, and ethanediamine. A control co‐oligomer (P2) possessing similar structure to P1 was also prepared, but in this case the OPE bears no side chains. P1 and P2 have been used for the fabrication of two fluorescent films, film 1 and film 2, respectively. Fluorescence studies demonstrated that the emission of film 1 is sensitive and selective to the presence of trace amounts of HCl in air. In contrast, film 2 shows no such response. The quenching has been attributed to the protonation of the imino groups within the oligomer chains, and the difference in the sensing behaviors of the two films was rationalized by supposing the existence of molecular channels in film 1. The proposed mechanism is supported by the results from additional experiments and theoretical calculations. Furthermore, the film as fabricated is robust, and thereby it is believed that film 1 has the potential to be developed into a new generation of sensitive and selective HCl sensor.